Supra-Acetabular Brown Tumor due to Primary Hyperparathyroidism Associated with Chronic Renal Failure - Rosaria M. Ruggeri; Emanuele Calamoneri; Antonia Russo; Alessandro Sindoni; Baldassarre Mondello; Maurizio Monaco; Michele A. Rosa; Sergio Baldari; Salvatore Benvenga; Alfredo Campennì; Francesco Trimarchi (The Scientific World Journal)
A 63-year-old woman presented to the Orthopedic Unit of our hospital complaining of right hip pain of 6 months'duration associated with a worsening limp. Her past medical history included chronic renal insufficiency. Physical examination revealed deep pain in the iliac region and severe restriction of the right hip's articular function in the maximum degrees of range of motion. X-rays and CT scan detected an osteolytic and expansive lesion of the right supra-acetabular region with structural reabsorption of the right iliac wing. 99mTc-MDP whole-body bone scan showed an abnormal uptake in the right iliac region. Bone biopsy revealed an osteolytic lesion with multinucleated giant cells, indicating a brown tumor. Serum intact PTH was elevated (1020 pg/ml; normal values, 12 62 pg/ml), but her serum calcium was normal (total = 9.4 mg/dl, nv 8.5–10.5; ionized = 5.0 mg/dl, nv 4.2–5.4) due to the coexistence of chronic renal failure. 99mTc-MIBI scintigraphy revealed a single focus of sestamibi accumulation in the left retrosternal location, which turned out to be an intrathoracic parathyroid adenoma at surgical exploration. After surgical removal of the parathyroid adenoma, PTH levels decreased to 212 pg/ml. Three months after parathyroidectomy, the imaging studies showed complete recovery of the osteolytic lesion, thus avoiding any orthopedic surgery. This case is noteworthy because (1) primary hyperparathyroidism was not suspected due to the normocalcemia, likely attributable to the coexistence of chronic renal failure; and (2) it was associated with a brown tumor of unusual location (right supra-acetabular region).